2020
DOI: 10.1016/j.annonc.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of an electronic symptom monitoring intervention based on the age of patients with advanced cancer

Abstract: Background: Symptom monitoring interventions enhance patient outcomes, including quality of life (QoL), health care utilization, and survival, but it remains unclear whether older and younger patients with cancer derive similar benefits. We explored whether age moderates the improved outcomes seen with an outpatient electronic symptom monitoring intervention.Patients and methods: We carried out a secondary analysis of data from a randomized trial of 766 patients receiving chemotherapy for metastatic solid tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…These interventions could potentially be adapted for caregivers of older patients with cancer. In fact, electronic symptom monitoring has been shown to improve patient outcomes [43][44][45] and could be further studied in caregivers of these patients. Our findings also have implications for the development of interventions targeting both prognostic understanding and mastery among caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…These interventions could potentially be adapted for caregivers of older patients with cancer. In fact, electronic symptom monitoring has been shown to improve patient outcomes [43][44][45] and could be further studied in caregivers of these patients. Our findings also have implications for the development of interventions targeting both prognostic understanding and mastery among caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…However, older adults may have increased barriers to the use of new technologies and unique issues related to digital literacy, warranting further examination of the digital divide and tailoring intervention to the older adult population. A recent secondary analysis by Nipp et al found that age moderated the beneficial effects of an electronic symptom monitoring intervention on the risk of emergency room visits and survival, thus highlighting important age-related differences in electronic health interventions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Nipp and colleagues found that older adults may not derive the same benefits from an electronic symptom monitoring intervention as younger adults. 32 Specifically, both the older and younger populations in the intervention arm had lower risks of hospitalization and better quality of life, but emergency room visits and survival were similar between the intervention and control arms in the older age group. This study highlights the need to tailor technologybased interventions to the unique needs of older adults.…”
Section: Emerging Data On the Use Of Digital Health Technologies For mentioning
confidence: 91%
“…The best current example of the latter is likely home-based ePRO monitoring, 31 although the robustness of this approach in older individuals with cancer is still being evaluated. 32…”
Section: Selection and Use Of Wearable Sensors In Oncology Practicementioning
confidence: 99%